Of women and salt eaudiobook A novel. - Garcia, Gabriela (Macmillan Audio, 2021)
AN INSTANT NEW YORK TIMES BESTSELLER A GOOD MORNING AMERICA BOOK CLUB PICK This program includes a bonus conversation between the author and Roxane Gay. A sweeping, masterful debut about a daughter's fateful choice, a mother motivated by her own past, and a family legacy that begins in Cuba before either of them were born In present-day Miami, Jeanette is battling addiction. Daughter of Carmen, a Cuban immigrant, she is determined to learn more about her family history from her reticent mother and makes the snap decision to take in the daughter of a neighbor detained by ICE. Carmen, still wrestling with the trauma of displacement, must process her difficult relationship with her own mother while trying to raise a wayward Jeanette. Steadfast in her quest for understanding, Jeanette travels to Cuba to see her grandmother and reckon with secrets from the past destined to erupt. From 19th-century cigar factories to present-day detention centers, from Cuba to Mexico, Gabriela Garcia's Of Women and Salt is a kaleidoscopic portrait of betrayals—personal and political, self-inflicted and those done by others—that have shaped the lives of these extraordinary women. A haunting meditation on the choices of mothers, the legacy of the memories they carry, and the tenacity of women who choose to tell their stories despite those who wish to silence them, this is more than a diaspora story; it is a story of America's most tangled, honest, human roots. A Macmillan Audio production from Flatiron Books " Of Women and Salt is a fierce and powerful debut. Garcia wields narrative power, cultivating true and profound work on migration, legacy, and survival."— Terese Marie Mailhot , bestselling author of Heart Berries "Gabriela Garcia captures the lives of Cuban women in a world to which they refuse to surrender and she does so with precision and generosity and beauty."— Roxane Gay , bestselling author of Hunger and Bad Feminist "[A] beautifully evocative first novel...This book is shaped, and given buoyancy, by Garcia's sharp prose and by Jeanette's ability to continue believing that the unexpected is possible, even as it repeatedly fails to materialize." — New York Times Book Review